THE DESIGN WEBSITE PROMOTION SYSTEM ON SPORT SHOE GALLERY MECROMEDIA USING DREAMWEAVER 8 - Dodi Hilamanda; Elly Agustina.,J.Skom,MMSI (Jurnal Sistem Informasi, 2008)
Writing is about a quick profile of How to promote so the public can find completeinformation.Under these circumstances, the writer made an application in accordance with currentprocedures, this application is expected to assist in overcoming any problems thatexist, to know how can find Sport Shoes Shop via the Internet.